Church Missionary Society Archives, 1877-1982 - Church Missionary Society (CMS) (1877)
Includes records on personalities: Rev. J. N. Campbell, Terence Lane , Rev. Canon Ling and Mrs Amey, J. K. Russell, Stella Purchas, Dr. Roy Billington, Maureen Moss, Robert A. Sparkes(Mr and Mrs), Apollo Kivebu laya, Pamella Goode etc; Committees and boards: Standing committee, Exe cutive committee, African committee of the Church Missionary Society, A frican committee etc; Staff and staffing: Recruits, attached staff, vac ancies, staff house repairs etc; Finance: correspondence, A.O.H account s and grants, building (grants and materials), accounts and budget etc; Education activities:Education administration,Activities in different provinces like Western province, Eastern etc; Medical activities:Staff and staffing, Hospitals like Mengo, Maseno, Kabarole etc; Church activi ties: Namirembe church, Church of the province of East Africa, activiti es on baptised christians, Ngogwe Kyagwe, Diocesan synod etc and Genera l records: Which include,records on building, Furniture, Lweza Rest Hou se, Uganda missionaries, correspondence, etc.
AR/CMS
English
Shelf no. 1 and 2
Keywords: Church Societies; Missionaries